Investigating the regulatory role of Anti-Müllerian Hormone in the growing follicles of a monovulatory species - Elfituri, Abdullatif (2016)
Evidence from recent research suggests that folliculogenesis is regulated by stage specific locally produced growth factors and hormones including mediators of proliferation, differentiation and angiogenesis. AMH has been identified as one of these potentially important local factors and in polyovulatory species has been implicated in the regulation of the follicles growth, throughout its developmental stages. However in monovulatory species, despite its circulating levels being use as a marker of ovarian reserve and its suggested link to the aetiology of PCOS, little is known about its role and the means of its control in the growing follicle. Using the sheep model, the over-riding objective of this research project was the further elucidation of the roles of AMH during the antral stages of follicular development in monovulatory species. It was hoped the work would also provide valuable insights into the aetiology of PCOS. The study has focussed on four main research goals: characterisation of GC and TCs in terms of AMH and AMHR2 expression; confirmation of the utilisation of a SMAD signal transduction pathway in GC and TCs; an androgen involvement in AMH production; and the elucidation of two putative mechanisms of AMH regulation.